High abundance of alkylated diamondoids, thiadiamondoids and thioaromatics in recently discovered sulfur-rich LS2 condensate in the Tarim Basin. (September 2018) - Zhu, Guangyou; Zhang, Ying; Zhang, Zhiyao; Li, Tingting; He, Nannan; Grice, Kliti; Neng, Yuan; Greenwood, Paul
Highlights: First characterization of condensate recently discovered in Bachu uplift. Wide distributions of OSC/diamondoid isomers resolved. Includes many additional isomers than previously detected in petroleum. TSR source of condensate correlated with deep Cambrian strata. Abstract: Molecular and stable sulfur isotopic (δ 34 S) analysis of petroleum recently discovered in the Bachu uplift of the Tarim Basin (China) was conducted to characterize the oil and assist future regional petroleum correlation studies. Sulfur-rich condensate from the Lower Ordovician – Upper Cambrian reservoir rock in the LS2 well showed abundant aromatic hydrocarbons and organic sulfur compounds. Extensive distributions of alkylated caged hydrocarbons (i.e., diamondoids) and caged sulfur compounds (thiadiamondoids), including many additional isomers not previously detected in petroleum, were resolved by GC × GC–MS analysis. The thiadiamondoid products and thioaromatics (i.e., benzothiophenes, dibenzothiophenes), also detected in LS2, products were attributed to a major thermochemical sulfate reduction (TSR) event, which resulted in elevated H2 S (3.66%) and dry gas in the condensate. TSR might also have contributed to the generally heavier δ 34 S values of the benzothiophenes (+26 to +28‰) compared to dibenzothiophenes (+20 to +27‰). The LS2 reservoir has no sulfate evaporites and the temperature (144 °C) is relatively low for TSR, implying that it is a secondary reservoir for migrated TSR-derived gas, possibly derived from deeper and hotter (>200 °C) Cambrian strata.